The language of angels : a story about the reinvention of Hebrew - Michelson, Richard; Gudeon, Karla (Watertown, MA : Charlesbridge, 2017)
Once there was a child without a friend. Ben-Zion's father insisted that his son speak only Hebrew, considered by some as the language of angels. But in the 1880s, the Jewish people who lived in Jerusalem spoke Yiddish or the languages of the places where they grew up. Hebrew hadn't been in everyday use for more than two thousand years, and adults said it could never be revived.
"This is the story of how one man and his son brought Hebrew back into common use. It's a story about how language changes and grows. And it's a story about how one person can make a difference"--Jacket.
Keywords: Ben-Yehuda, Eliezer, -- 1858-1922 -- Juvenile literature; Hebrew language -- Revival -- Juvenile literature; Ben-Yehuda, Eliezer, -- 1858-1922.; Hebrew language -- Revival